Shear Strengthening of Deep Beams Using Polymer-Based CFRP Bars via the Near-Surface Mounting (NSM) Technique - Azeez, Alyaa Abdulrazzaq (Journal of Research Updates in Polymer Science, 2026)
Near-surface-mounted strengthening with polymer-based carbon fiber-reinforced polymer (CFRP) bars has been proved as one of the efficient techniques in enhancing the shear capacity of reinforced concrete RC deep beams. This paper presents an experimental investigation on the shear behavior of RC deep beams strengthened with NSM CFRP bars. Five identical RC deep beam specimens with the same geometry and internal steel reinforcement were tested under two-point loading. One specimen was left un-strengthened as a control beam; while four specimens have been strengthened by CFRP bars embedded in the shear zone with two orientations, 0°/90° and 45°/135°, and two spacing configurations, 100 and 150 mm. Response parameters of prime interest included first shear cracking load, ultimate shear capacity, crack pattern, and mid-span deflection. The findings of the experiment demonstrated that NSM CFRP strengthening improved the shear performance of deep beams; depending on the orientation and spacing of the CFRP bars, shear capacity augmentation ranged from about 14% to 47% in comparison to the control specimen. Additionally, at similar load levels, strengthened beams demonstrated a 10% to 40% decrease in mid-span deflections and fracture widths. The test results demonstrate how well polymer-based CFRP bars inserted using the NSM technology improve the stiffness and shear strength of RC deep beams.